From Innovation to Market Leadership: A Case Study of iD Fresh Foods’ Business Strategy - Roy, Somnath (Journal of Global Economy, Business and Finance, 2025)
The ready - to - cook (RTC) segment has revolutionized the landscape of the packed food domain with its disruptive innovation and product offerings. With the advancement in technology to preserve and lock the natural flavors of foods and with the potential to possess the taste as close to eating a freshly prepared homemade delicacy, these RTC products have contributed significantly to the spike in demand and customer loyalty. This work emphasizes presenting the RTC space and how this segment has been a launchpad for ‘iD Fresh Foods’, a famous company that has been thriving seamlessly, rising to glory at international levels. The brand’s strategies and its driving factors to help the company achieve various milestones are discussed in detail.